2022
DOI: 10.1126/science.add7574
|View full text |Cite
|
Sign up to set email alerts
|

Molecular glue CELMoD compounds are regulators of cereblon conformation

Abstract: Cereblon (CRBN) is a ubiquitin ligase (E3) substrate receptor protein co-opted by CRBN E3 ligase modulatory drug (CELMoD) agents that target therapeutically relevant proteins for degradation. Prior crystallographic studies defined the drug-binding site within CRBN’s thalidomide-binding domain (TBD), but the allostery of drug-induced neosubstrate binding remains unclear. We performed cryo–electron microscopy analyses of the DNA damage-binding protein 1 (DDB1)–CRBN apo complex and compared these structures with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 32 publications
6
70
1
Order By: Relevance
“…Unlike most other DCAF proteins, DCAF16 does not contain a canonical WD40 propeller 34 , and instead is a relatively unstable protein predicted to be largely unstructured. It is noteworthy that our structural studies suggest a high degree of conformational flexibility, similar to findings from studies of CRBN [35][36][37] , and we speculate that such structural plasticity in a ligase can facilitate glue activity. A central challenge for the development of molecular glue degraders is the need for approaches for rational drug design and discovery 38 .…”
Section: Discussionsupporting
confidence: 85%
“…Unlike most other DCAF proteins, DCAF16 does not contain a canonical WD40 propeller 34 , and instead is a relatively unstable protein predicted to be largely unstructured. It is noteworthy that our structural studies suggest a high degree of conformational flexibility, similar to findings from studies of CRBN [35][36][37] , and we speculate that such structural plasticity in a ligase can facilitate glue activity. A central challenge for the development of molecular glue degraders is the need for approaches for rational drug design and discovery 38 .…”
Section: Discussionsupporting
confidence: 85%
“…The linker has a key impact on the molecular glue function. Recently, the structural mechanism for this function of IMiDs was elucidated . The authors studied three molecules with different activities for ubiquitinylation of the neosubstrate Ikaros: compounds 12 (moderate), 55 (CC-220, potent), and 56 (CC-92480, most potent).…”
Section: Protac Design Strategymentioning
confidence: 99%
“…Recently, the structural mechanism for this function of IMiDs was elucidated. 79 The authors studied three molecules with different activities for ubiquitinylation of the neosubstrate Ikaros: compounds 12 (moderate), 55 (CC-220, potent), and 56 (CC-92480, most potent). Their data showed that pomalidomide induced 20% of CRBN to be closed, and compound 55 induced 50% of CRBN to be closed.…”
Section: Molecular Glue Functionmentioning
confidence: 99%
“…Finally, MGDs may also function from an allosteric site . In this case, the small molecule does not participate directly in the interaction.…”
Section: Enabling Prospective Degrader Discoverymentioning
confidence: 99%
“…259 Finally, MGDs may also function from an allosteric site. 260 In this case, the small molecule does not participate directly in the interaction. Rather, it exposes or modifies a PPI interface by binding to a distant pocket that stabilizes a (non-native) conformation of the protein.…”
Section: Leveraging Low-affinity Protein−protein Interactionsmentioning
confidence: 99%